Redefinition and partial revision of the genus Stenaelurillus Simon, 1886 (Arachnida, Araneae, Salticidae) - Logunov, Dmitri V.; Azarkina, Galina N. (European Journal of Taxonomy, 2018)
This paper presents an improved diagnosis and definition of the genus Stenaelurillus Simon, 1886, with new taxonomic and faunistic data for 23 species. The genera Microheros Wesołowska & Cumming, 1999 and Mashonarus Wesołowska & Cumming, 2002 are synonymized with Stenaelurillus. Six new species are described: Stenaelurillus bandama sp. nov. (♂♀, from Côte d’Ivoire), S. belihuloya sp. nov. (♂, from Sri Lanka), S. jocquei sp. nov. (♂♀, from Cameroon), S. pseudoguttatus sp. nov. (♂, from Namibia), S. senegalensis sp. nov. (♂♀, from Senegal), and Stenaelurillus siyamae sp. nov. (♀, from Sudan). Lectotypes are designated for two species: S. albopunctatus Caporiacco, 1949 (♂) from Kenya and S. werneri Simon, 1906 (♀) from South Sudan. Six new combinations are proposed: Aelurillus ambiguus (Denis, 1966), comb. nov. (ex Stenaelurillus); Evarcha werneri (Simon, 1906), comb. nov. (ex Stenaelurillus); Phlegra davidi (Caleb, Mungkung & Mathai, 2015), comb. nov. (ex Mashonarus); Stenaelurillus brandbergensis (Wesołowska, 2006), comb. nov. (ex Mashonarus); Stenaelurillus guttatus (Wesołowska & Cumming, 2002), comb. nov. (ex Mashonarus); and S. termitophagus (Wesołowska & Cumming, 1999), comb. nov. (ex Microheros). Two species names are synonymized: Evarcha elegans Wesołowska & Russell-Smith, 2000 with E. werneri comb. nov.; and Aelurillus sahariensis Berland & Millot, 1941 with Stenaelurillus nigricaudus Simon, 1886. The female of S. fuscatus Wesołowska & Russell-Smith, 2000 is described for the first time.